Answer:
(3y-2)^2
Explanation:
To factor the polynomial, find the binomials which multiply to make it. This can be done for any polynomial
by finding numbers that multiply to a*c and add to b.
a*c=36 b=-12
36: 1, 2, 3, 4, 6. 6. 9, 12, 18, 36
Since -6*-6 = 36 and -6 + -6 = -12, split -12y in
to
.
Next, factor by grouping by finding GCF between pairs of terms:
![(9y^2-6y)+(-6y+4)\\3y(3y-2)-2(3y-2)\\(3y-2)(3y-2)\\(3y-2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yfl0eextv74b0vuaehlh434ro856xx6y0g.png)
(3y-2)^2 is the solution.